Peran Orang Tua Dalam Meningkatkan Motivasi Belajar Siswa Di SMA Negeri 1 Sianjur Mula Mula - Sagala, Cumiwati; Pardede, Sanggam; Siahaan, Mian (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to examine the role of parents in enhancing students’ learning motivation at SMA Negeri 1 Sianjur Mula Mula. The research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The informants consisted of 9 students as key informants, along with 6 parents and 3 teachers as supporting informants. The findings reveal that parents play a significant role in supporting students’ motivation to learn, both as motivators who provide encouragement, advice, and small rewards; as facilitators who provide learning resources and facilities; as supervisors and mentors who arrange study schedules, limit distractions, and communicate with teachers; and as role models who instill discipline, hard work, honesty, and responsibility. In addition, parents create a comfortable home learning environment. The study concludes that consistent parental involvement has a strong impact on improving students’ enthusiasm, self-confidence, and academic achievement.